2014
DOI: 10.1002/2014gl060212
|View full text |Cite
|
Sign up to set email alerts
|

A new health check of the ozone layer at global and regional scales

Abstract: In this study, we provide a new perspective on the current state of the ozone layer using a comprehensive long-term total ozone data record which has been recently released within the framework of the European Space Agency's Climate Change Initiative. Based on a multivariate regression analysis, we disentangle various aspects of ozone change and variability on global and regional scales, thus enabling the monitoring of the effectiveness of the Montreal Protocol. Given dominant natural variability the expected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 59 publications
7
29
0
Order By: Relevance
“…When they use the EESC proxy, the trend is increasing with latitude so that at the Lauder latitude it reaches about 4-5 DU decade −1 . Our non-significant trends at Jungfraujoch, Izaña and Lauder, and positive trend at Wollongong are also in agreement with the recent study of Coldewey-Egbers et al (2014), which provides trends using a similar period (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013) of merged satellite data sets. For Wollongong, since the total column positive trend is due to the ozone trends in the lower and middle stratosphere, it cannot be attributed unambiguously to the EESCs decline.…”
Section: Total Columnssupporting
confidence: 93%
“…When they use the EESC proxy, the trend is increasing with latitude so that at the Lauder latitude it reaches about 4-5 DU decade −1 . Our non-significant trends at Jungfraujoch, Izaña and Lauder, and positive trend at Wollongong are also in agreement with the recent study of Coldewey-Egbers et al (2014), which provides trends using a similar period (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013) of merged satellite data sets. For Wollongong, since the total column positive trend is due to the ozone trends in the lower and middle stratosphere, it cannot be attributed unambiguously to the EESCs decline.…”
Section: Total Columnssupporting
confidence: 93%
“…Stolarski et al, 1991Stolarski et al, , 2006Fioletov et al, 2002;Brunner et al, 2006;WMO, 2007;Mäder et al, 2007;Harris et al, 2008;Chehade et al, 2014;Coldewey-Egbers et al, 2014) and UV radiation calculations at the Earth's surface (Lindfors et al, 2009;Krzyścin, 2008). Such an ozone data set is also important for quantifying ozone depletion and detecting the first signs of recovery (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The WMO assessment concluded that, at most latitudes, it is not yet possible to determine a statistically significant increase in total column ozone (lower stratosphere) because the expectedly small trends are masked by large interannual variability ( Fig. 2.43; see also Chehade et al 2014;Coldewey-Egbers et al 2014). In the tropics no discernible long-term stratospheric trends have been observed for the entire period.…”
mentioning
confidence: 99%
“…In the tropics no discernible long-term stratospheric trends have been observed for the entire period. Note that trends in tropical tropospheric ozone can potentially mask stratospheric trends in tropical total columns (Shepherd et al 2014) and there is evidence that decadal trends in the ENSO may have produced tropospheric ozone increases in some tropical regions during the past two decades ( Coldewey-Egbers et al 2014).…”
mentioning
confidence: 99%